Reversal of hepatocyte senescence after continuous in vivo cell proliferation. Issue 1 (28th May 2014) - Wang, Min‐Jun; Chen, Fei; Li, Jian‐Xiu; Liu, Chang‐Cheng; Zhang, Hai‐Bin; Xia, Yong; Yu, Bing; You, Pu; Xiang, Dao; Lu, Lian; Yao, Hao; Borjigin, Uyunbilig; et al.
<x xml:space="preserve">Abstract</x> A better understanding of hepatocyte senescence could be used to treat age‐dependent disease processes of the liver. Whether continuously proliferating hepatocytes could avoid or reverse senescence has not yet been fully elucidated. We confirmed that the livers of aged mice accumulated senescent and polyploid hepatocytes, which is associated with accumulation of DNA damage and activation of p53‐p21 and p16ink4a‐pRB pathways. Induction of multiple rounds continuous cell division is hard to apply in any animal model. Taking advantage of serial hepatocyte transplantation assays in the fumarylacetoacetate hydrolase‐deficient (Fah−/−) mouse, we studied the senescence of hepatocytes that had undergone continuous cell proliferation over a long time period, up to 12 rounds of serial transplantations. We demonstrated that the continuously proliferating hepatocytes avoided senescence and always maintained a youthful state. The reactivation of telomerase in hepatocytes after serial transplantation correlated with reversal of senescence. Moreover, senescent hepatocytes harvested from aged mice became rejuvenated upon serial transplantation, with full restoration of proliferative capacity. The same findings were also true for human hepatocytes. After serial transplantation, the high initial proportion of octoploid hepatocytes decreased to match the low level of youthful liver. Conclusion: These findings suggest that the hepatocyte "ploidy conveyer" is regulated differently during aging and regeneration. The findings of reversal of hepatocyte senescence could enable future studies on liver aging and cell therapy. (Hepatology 2014;60:349–361)